Christology in the Fourth Gospel: Redaction-Critical Perspectives - Fortna, Robert Tomson (New Testament studies, 1975)
At the start, a definition of limits:There is no attempt in what follows to give a total view of Johannine christology. We shall concentrate mainly on the narrative materials in the gospel, for it is there that redaction-critical work now seems most practicable; consequently, our sights can hardly be global. At the same time, however, we do not limit ourselves to the uppermost layer of christology in the narratives, for we shall be seeking to set the evangelist's thought in sharper perspective by the very process of comparing it - and often contrasting it - to the tradition, more specifically the source, on which he depends. Depth, then, more than breadth, will be our aim; depth such as we can gain from a few test bores into the Johannine terrain.